Reversible and regionally selective downregulation of brain cannabinoid CB1 receptors in chronic daily cannabis smokers - Hirvonen, J; Goodwin, R S; Li, C-T; Terry, G E; Zoghbi, S S; Morse, C; Pike, V W; Volkow, N D; Huestis, M A; Innis, R B (Molecular psychiatry, 2012)
Chronic cannabis (marijuana, hashish) smoking can result in dependence. Rodent studies show reversible downregulation of brain cannabinoid CB 1 (cannabinoid receptor type 1) receptors after chronic exposure to cannabis. However, whether downregulation occurs in humans who chronically smoke cannabis is unknown. Here we show, using positron emission tomography imaging, reversible and regionally selective downregulation of brain cannabinoid CB 1 receptors in human subjects who chronically smoke cannabis. Downregulation correlated with years of cannabis smoking and was selective to cortical brain regions. After ∼4 weeks of continuously monitored abstinence from cannabis on a secure research unit, CB 1 receptor density returned to normal levels. This is the first direct demonstration of cortical cannabinoid CB 1 receptor downregulation as a neuroadaptation that may promote cannabis dependence in human brain.